Performance Analysis of Service System in the Pediatric Clinic Department at Rumah Sakit Umum Daerah (RSUD) Sumedang - Annisa, Diana; Supian, Sudradjat; Nahar, Julita (iora, 2023)
A service is considered good if it can provide fast service so that customers are not left waiting for too long. If a service has a long queue, then causing customers to wait for a long time, their satisfaction and trust levels may decrease. Rumah Sakit Umum Daerah (RSUD) Sumedang offers various outpatient services, including a pediatric clinic. Almost every day, a significant number of patients come to the pediatric clinic, resulting in considerable waiting time for patients. The service discipline used is First Come First Serve, and the service system falls under the multi-phase category, where each patient has to go through several stages to receive optimal service. This research will focus on the service system in the pediatric clinic at each stage, starting from registration, examination by the doctor, to medication collection at the pharmacy. The research findings indicate that the workload at the pharmacy counter is very high, while it is significantly low at the registration counter, resulting in suboptimal performance of the service system at these two stages. The performance of the service system can be improved by reducing service facilities at the registration counter and adding resources at the pharmacy counter.Â